Analisis dan Overview Model Peningkatan Mutu Marketing 4.0 di MTs Swasta Syamsudhuha - Muslina Jamil; Syarifah Rahmah (Idarah (Jurnal Pendidikan dan Kependidikan), 2021)
This study aims to analyze a model for improving the quality of marketing 4.0 in Islamic educational institutions. This research uses descriptive qualitative research method by analyzing. The data collection method uses participant observation, documentation, and references to journals on the internet. Data analysis with data reduction, data presentation, and drawing conclusions. The results showed that the management of Islamic education marketing is very important and an integral part of organizing and maintaining the existence of Islamic educational institutions. In an Islamic education institution, it must have a marketing person who is capable of mastering technology, because marketing management is very important in the success of the vision and mission of Islamic education institutions. In Islamic education institutions, it is necessary to make new innovations in marketing educational services in order to be able to face the challenges of the times and the competition in the era of globalization.